The Categorical Organization of Semantic and Lexical Knowledge in the Brain - Guido Gainotti (Behavioural Neurology)
In recent years several papers have shown that different verbal and non-verbal semantic categories can be selectively disrupted by brain damage and that consistent anatomical localizations correspond to each category-specific semantic disorder. This paper aims to suggest that the brain regions typically damaged in a given type of category-specific semantic disorder might be critically involved in processing the kind of information which mainly contributes to organizing that semantic category and to distinguishing among its members. This general hypothesis is discussed taking into account: (a) comprehension and production of object names (nouns) and of action names (verbs) in agrammatic and in anomic aphasic patients; (b) verbal and non-verbal identification of body parts; (c) verbal and non-verbal identification of living beings and of man made artefacts.